A Theory of Economic Oscillations - Moore, Henry Ludwell (Quarterly Journal of Economics, 1926)
Introduction, 1. — Walrasian equations, 3. — Partial elasticity of demand, 9. — Partial elasticity of supply, 15. — Coefficients of production, 17. — A moving general equilibrium, 23. — Economic oscillations, 26. — Conclusions, 28.